Multivariable non-invasive association of isocitrate dehydrogenase mutational status in World Health Organization grade II and III gliomas with advanced magnetic resonance imaging T2 mapping techniques. Issue 2 (April 2020) - Kern, Maike; Auer, Timo A; Fehrenbach, Uli; Tanyildizi, Yasemin; Picht, Thomas; Misch, Martin; Wiener, Edzard
Aim: To investigate multivariable analyses for noninvasive association of the isocitrate dehydrogenase (IDH) mutational status in grade II and III gliomas including evaluation of T2 mapping-sequences. Methods: Magnetic resonance imaging (MRI) examinations with histopathologically proven World Health Organization grade II and III gliomas were retrospectively enrolled. Multivariate receiver operating characteristics (ROC) analyses to associate IDH mutational status were performed containing quantitative T2 mapping analyses and qualitative characteristics (sex, age, localization, heterogeneity, oedema, necrosis and diameter). Relaxation times were calculated pixelwise by means of standardized ROI analyses. Interobserver variability also was tested. Results: Out of 32 patients (mean age: 50.7 years; range: 32–83), nine had grade II gliomas and 24 grade III, while 59.5% showed a positive IDH mutated state (IDHm) and 40.5% were wildtype (IDHw). Multivariable ROC analyses were calculated for relaxation time and range, localization and age with a cumulative 0.955 area under the curve (AUC) ( p < 0.001), while central T2-relaxation time had by far the highest single variable sensitivity (AUC: 0.873; range: 0.762; age: 0.809; localization: 0.713). Age (cut off: 49 years; p = 0.031) and localization ( p = 0.014) were the only qualitative parameters found to be significant as IDHw gliomas were older and IDHm gliomas were preferentially located fronto-temporal. Conclusions: This is the first study evaluating quantitative T2 mapping sequences for association of the IDH mutational status in grade II and III gliomas demonstrating an association between relaxation time and mutational status. Analyses of T2 mapping relaxation times may even be suitable for predicting the correct IDH mutational state. Prognostic accuracy increases significantly in predicting the correct mutational state when combing T2 relaxation time characteristics and the qualitative MRI features age and localization.